Nondenaturing polyacrylamide gel electrophoresis to study the dissociation of the p53·MDM2/X complex by potentially anticancer compounds. Issue 24 (30th October 2015) - Sgammato, Roberta; Desiderio, Doriana; Lamberti, Anna; Raimo, Gennaro; Novellino, Ettore; Carotenuto, Alfonso; Masullo, Mariorosario
Abstract : A new analytical method to study the dissociation of the complexes between the oncosuppressor p53 and its negative modulators murine double‐minute protein 2 (MDM2) or MDMX, is proposed. This technique is reliable to determine the dissociative power exerted by small molecules on the complex taking advantage of the appearance of migrating MDM2 or MDMX in a native polyacrylamide gel, when inhibitors are added to the complex mixture. Therefore, we propose this new approach to easily screen library of compounds, with potential pharmacological anticancer activity.